Vaccine Interactions With the Infant Microbiome: Do They Define Health and Disease? - Ruck, Candice E.; Odumade, Oludare A.; Smolen, Kinga K. (Frontiers in Pediatrics, 2020)
Over the past decade, there has been a growing awareness of the vital role of the microbiome in the function of the immune system. Recently, several studies have demonstrated a relationship between the composition of the microbiome and the vaccine-specific immune response. As a result of these findings, the administration of probiotics has been proposed as a means of boosting vaccine-specific immunity. Early results have so far been highly inconsistent, with little evidence of sustained benefit. To date, a precise determination of the aspects of the microbiome that impact immunity is still lacking, and the mechanisms of action are also unknown. Further investigations into these questions are necessary to effectively manipulate the microbiome for the purpose of boosting immunity and enhancing vaccine-specific responses in infants. In this review, we summarize recent studies aimed at altering the neonatal gut microbiome to enhance vaccine responses and highlight gaps in knowledge and understanding. We also discuss research strategies aimed at filling these gaps and developing potential therapeutic interventions.